Increasing Doctors’ Employment in Companies by Tailored Teaching and Matchmaking Actions - Kunttu, Leena; Neuvo, Yrjö; Tikkanen, Seppo (Lappeenranta University of Technology, 2022)
Active industry - academia interaction is of fundamental importance in addressing our global challenges. In this paper, we present two programs that lower the barrier between these two domains. The experimental educational program for doctoral students is an adaptation of top-level management training program to the academic environment. The matchmaking program between a company and a young doctor provides a low entry barrier to companies to test new ideas with the doctor and build new competences by hiring the doctor. In this program, the funding for the research phase is covered by a foundation and the development phase by the company.
Keywords: business foresight; collaboration; doctoral education; global challenges; global perspective; industry-academia interaction; management training; product development; Teamwork; innovations